On the ideals of extended quasi-nilpotent Banach algebras - Morteza Seddighin (International Journal of Mathematics and Mathematical Sciences)
Given a quasi-nilpotent Banach algebra A, we will use the results of Seddighin [2], to study the properties of elements which belong to a proper closed two sided ideal of A¯ and A¯¯. Here A¯ is the extension of A to a Banach Algebra with identity.